PERANCANGAN MEREK DAN KEMASAN GELAMAI MAK LENI PAYAKUMBUH - ARINKA DIAN NUGRAHA, Hendra Afriwan, S.Sn., M.Sn., Eliya Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
Gelamai Mak Leni is a home made gelamai industry which is owned by Mr. Riswandi and Ms. Musleni. Gelamai Mak Leni has been estabilished since 2012 and it is located in Koto Baru, Kec. Simalanggang, Kab. Lima Puluh Kota, Payakumbuh. The Brand and Packaging Design of Gelamai Mak Leni was based on the visual identitiy and the undefinite, yet inconsistency of the packaging that represents the industry of Gelamai Mak LeniThe design method was started from datas collecting, interviewing, and observing. In order to find the problem and the identification of the problem, it was being analysed by using the SWOT theory (SWOT), and further by using analysis data cinclusion and creative approach. In designing the brand and packaging of Gelamai Mak Leni (Mak Leni’s Gelamai), the writer indicated the verbal and visual message to people though branding and packaging.The primary media in this design were brand and packaging. Beside the primary media, this design was also being completed with the secondary media such as paper bag, sticker, name card, mug, printed t-shirt, stamp, pin, receipt, x-banner, calender, and clock.Keywords: Brand, Packaging, Gelamai Mak Leni, Media.